Crack initiation prediction eliminating the influence of loading path change: Prediction strategy and model validation. (1st October 2020) - Zhang, Wen; Yang, Huachao; Zhuang, Xincun; Ma, Yan; Zhao, Zhen
Highlights: Stress-based failure limit and strain-based damage accumulation law are combined. Damage evolution path switches from one to another when loading path changes. Loading path dependency in general strain-based failure model could be eliminated. Crack initiation under variable-path-loading conditions could be well predicted. Abstract: To improve failure prediction under variable-path-loading conditions, a model combining the stress-based failure limit (SFL) and strain-based damage accumulation (SDA) law, which is named as combined stress-strain-based failure model (CSSFM), was proposed. The integration of SFL enables the proposed model to determine the analytical failure stress and strain, which will be embedded in SDA law, without the influence of loading-path change. The model predicted the failure according to the accumulated damage rather than the analytical failure stress or strain. To evaluate the applicability of the proposed model, parallel simulation was carefully conducted corresponding to a series of two-stage loading tests, namely torsion-tension and compression-torsion tests, reported in the previous publication (Zhuang et al., 2016). Numerical simulations which involved Chaboche combined hardening model with three back stresses were employed to provide necessary variables related to parameter identification of CSSFM. The simulation result was validated by a good accordance between the numerical and experimental load-stroke curves. It is revealed that with the Chaboche combined hardening model, the integrated CSSFM exhibited reasonable performance in describing failure behavior under the reported two-stage loading conditions. Graphical abstract: Image, graphical abstract